Determinant Analysis of Corporate Social Responsibility Disclosure in Food and Beverages Company - Dwi Cahyono; Intan Sarifa Nuraeni (Universitas Muhammadiyah Sorong, 2021)
The environmental sustainability has a big and important role in the success of a company. Organizational benchmarks can be seen from the company's financial performance which is allocated for Corporate Social Responsibility (CSR) disclosure. Corporate Social Responsibility (CSR) Disclosure is the company's concern for its surrounding environment, which will affect the sustainability of the company. Good companies regularly disclose their Corporate Social Responsibility (CSR). Many studies have been conducted by examining the determinants in Corporate Social Responsibility (CS ) disclosure. However, several things do not show that the research have a big effect on Corporate Social Responsibility (CSR ) disclosure. This decision making is based on existing theory.Â